Neighbourhood satisfaction in rural resettlement residential communities: the case of Suqian, China. Issue 8 (14th September 2022) - Gao, Xing; Wang, Zijia; Cao, Mengqiu; Liu, Yuqi; Zhang, Yuerong; Wu, Meiling; Qiu, Yue
Abstract: Against the background of large-scale urbanisation and rural land expropriation, rural resettlement residential housing has been built to accommodate local rural residents in the peripheral areas of China. To explore the context-specific policy implications for improving neighbourhood satisfaction (NS) of residents in rural resettlement residential communities (RRRCs), this paper examines the determinants of NS, and their spatial effects, in rural resettlement residential neighbourhoods using Suqian, in Jiangsu Province, as a case study. This study contributes to the current literature in two ways: it constitutes the first attempt to examine NS among RRRCs; second, our spatial model helps to gain further understanding of horizontal and vertical spatial dependence effects. Our results indicate that income, gender, age, family structure, number of years living in a community, transport and architectural age all have significant effects on NS in RRRCs.